Control analysis of virotherapy chaotic system. Issue 1 (31st December 2022) - Iqbal, Javaria; Ahmad, Salman; Marwan, Muhammad; Rafiq, Ayesha
Abstract : In this work, we consider a chaotic system that plays a vital role in the treatment of cancer by injection of a virus externally. Due to the sensitivity of this disease, most of its treatments are highly risky. Therefore, we have designed control inputs using adaptive and passive control techniques for virotherapy. Both controllers are designed to bring global stability to the cancer system with the aid of a quadratic Lyapunov function. Furthermore, we use simulations to verify our controllers. Moreover, we show that our adaptive control technique gives better results in comparison.